231 DOES RESIDENCY TRAINING IMPROVE PERFORMANCE OF PHYSICAL EXAMINATION SKILLS?. (1st January 2005) - Willett, L. L.; Estrada, C. A.; Castiglioni, A.; Massie, F. S.; Heudebert, G. R.; Centor, R. M.
Abstract : Purpose: To determine whether graduating postgraduate year (PGY)-3 residents have better physical examination skills and comfort level compared to incoming PGY-1 residents. Methods: We used a five station Objective Structured Clinical Examination (OSCE) to assess physical examination skills. The stations included cases of pneumonia, congestive heart failure (CHF), ascites, shoulder pain, and back pain. Simulated patients scored performance with task-specific checklists (score range: 0-100%). Residents assessed their comfort level on a 5-point Likert scale (1 = low, 5 = high). We used nonparametric analysis to compare groups. Results: PGY-3 residents (n = 8) had significantly increased overall performance compared to PGY-1 residents (n = 16) for all stations combined (p = .03). A nonsignificant trend was seen for each individual station with improved median performance of PGY-3 vs PGY-1 residents: pneumonia (65% vs 54%), CHF (82% vs 73%), ascites (85% vs 69%), shoulder pain (68% vs 57%), and back pain (84% vs 75%). Additionally PGY-3 residents had statistically increased comfort level overall (p = .003) and for each individual station (all p < .05). Conclusions: Our study suggests that departing PGY-3 residents have better physical examination skills and comfort level as compared to incoming PGY-1 residents, a reassuring finding for program directors reinforcing the apprenticeship model. Whether the improved subjective comfort level exceeds objective performance is unclear. (Table )